2023
DOI: 10.7759/cureus.35527
|View full text |Cite
|
Sign up to set email alerts
|

Adult-Onset IgA Vasculitis Associated With Pulmonary-Renal Syndrome Following COVID-19 Infection: A Case Report and Literature Review

Abstract: Immunoglobulin A (IgA) vasculitis, also known as Henoch-Schönlein purpura (HSP), is an immune complexmediated inflammation of small blood vessels that leads to tissue destruction with or without organ damage. We described a case of a 41-year-old otherwise healthy female who presented with an ascending rash distributed on both lower extremities and arthralgia. Blood testing revealed high blood urea nitrogen (BUN), creatinine, and inflammatory markers, as well as a negative autoimmune panel. Urinalysis revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…For example, recently, there have been reports on post-COVID-19 viral infections and their relations to IgAV. Two adult-onset post-COVID IgAV cases reported similar petechial lesions and palpable purpura presentations; however, they both survived with the usage of corticosteroids [5,6]. On the basis of treatment, one case utilized further azathioprine whereas the other used intravenous immunoglobulin and plasma exchange [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, recently, there have been reports on post-COVID-19 viral infections and their relations to IgAV. Two adult-onset post-COVID IgAV cases reported similar petechial lesions and palpable purpura presentations; however, they both survived with the usage of corticosteroids [5,6]. On the basis of treatment, one case utilized further azathioprine whereas the other used intravenous immunoglobulin and plasma exchange [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Two adult-onset post-COVID IgAV cases reported similar petechial lesions and palpable purpura presentations; however, they both survived with the usage of corticosteroids [5,6]. On the basis of treatment, one case utilized further azathioprine whereas the other used intravenous immunoglobulin and plasma exchange [5,6]. One multi-center randomized trial demonstrated that the addition of cyclophosphamide to corticosteroids did not improve disease remission nor active visceral involvement when compared to corticosteroids alone for treatment [7].…”
Section: Discussionmentioning
confidence: 99%